Study of sedative activity of different extracts of Kaempferia galanga in Swiss albino mice - Ali, Mohammad Shawkat; Dash, Pritesh Ranjan; Nasrin, Mahmuda (© 2015 BioMed Central Ltd., 2016)
This article was published in BMC Complementary and Alternative Medicine [© 2015 BioMed Central Ltd.] and the definite version is available at: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC4443623/ The article website is at: http://www.biomedcentral.com/